Associations between size at birth and size at 6 years among preterm infants: a retrospective cohort study. Issue 1 (27th February 2022) - Awata, Kentaro; Shoji, Hiromichi; Santosa, Irena; Ikeda, Naho; Murano, Yayoi; Ohkawa, Natsuki; Nishizaki, Naoto; Hisata, Ken; Kantake, Masato; Obinata, Kaoru; Shimizu, Toshiaki
Abstract: Background: Little is known about the relationship between fetal growth and size at school age in children born prematurely. We evaluated the relationships between gestational age and anthropometric z‐scores at birth and size at 6 years of age in very‐low‐birthweight infants born at <30 weeks' gestation. Methods: We collected data from the medical records of 187 preterm children at birth and 6 years of age. We evaluated correlations between gestational age and z‐scores for weight, body length, and head circumference at birth and z‐scores for weight, height, and body mass index at 6 years of age. Results: Simple regression analysis showed that, in boys and the overall group, gestational age and z‐scores for weight, body length, and head circumference at birth had significant association with z‐scores for weight, height, and body mass index at 6 years of age. No significant associations were found in girls, except for weight z‐scores at 6 years with gestational age and head circumference z‐scores at birth. Multiple regression analysis showed that gestational age and length z‐score at birth were significantly and independently associated with weight and height z‐score at 6 years. Gestational age was also significantly and independently associated with body mass index z‐score at 6 years. Conclusion: Gestational age and fetal growth in length (assessed with the birth‐length z‐score) were associated with anthropometric z‐scores at 6 years in very‐low‐birthweight children born at <30 weeks of gestation, especially in boys.